Music consumption among English speaking teenage girls in the city of Montreal - Giles, Jennifer (Université Carleton, 1987)
Music Consumption among English Speaking Teenage Girls in the City of Montreal

Exposition au monastère des Ursulines de Québec - Grégoire-Reid, Claire; Vézina-Demers, Micheline (Les Cahiers de l'ARMuQ, 1987)